2017
DOI: 10.1002/jcc.25088
|View full text |Cite
|
Sign up to set email alerts
|

Hyperconjugative effects in π‐hydrogen bonding: Theory and experiment

Abstract: Density functional theory computations with the B3LYP/6-311++G(2df,2p) method and IR spectroscopy are employed in investigating the properties of twenty π-hydrogen bonded complexes between substituted phenols and hexamethylbenzene. All complexes possess T-shaped structures. The methyl hyperconjugative effects on interactions energies and OH stretching frequencies are estimated via comparisons with previously reported theoretical and experimental results for analogous phenol complexes with benzene. The theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…For the stronger electron-donating NH 2 , NHCH 3 , and N­(CH 3 ) 2 groups, only the Hirshfeld charges predict correctly the expected transfer of a negative charge from the substituents to the ring. In a recent study, we discussed the charge transfer and methyl hyperconjugative effects in a theoretical and spectroscopic investigation of π-hydrogen bonding complexes between substituted phenols and hexamethylbenzene …”
Section: Resultsmentioning
confidence: 99%
“…For the stronger electron-donating NH 2 , NHCH 3 , and N­(CH 3 ) 2 groups, only the Hirshfeld charges predict correctly the expected transfer of a negative charge from the substituents to the ring. In a recent study, we discussed the charge transfer and methyl hyperconjugative effects in a theoretical and spectroscopic investigation of π-hydrogen bonding complexes between substituted phenols and hexamethylbenzene …”
Section: Resultsmentioning
confidence: 99%
“…The reactivity of aromatic molecules is usually associated with the variations of electron densities at the ring sites. 44−46 Our recent investigations 59,60 have shown that the shifts of O−H stretching frequencies upon π-hydrogen bonding may be correlated with the electron densities associated with the arene π-electron system. Stoyanov and Read 62 have emphasized the relationship between basicities of organic compounds and N− H stretching frequency shifts upon π-hydrogen bonding.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The basic hypothesis in the present research considers the expected link between the shifts in the phenol O–H stretching frequency upon π-hydrogen bonding with arene derivatives and the electron densities over the aromatic ring. The reactivity of aromatic molecules is usually associated with the variations of electron densities at the ring sites. Our recent investigations , have shown that the shifts of O–H stretching frequencies upon π-hydrogen bonding may be correlated with the electron densities associated with the arene π-electron system. Stoyanov and Read have emphasized the relationship between basicities of organic compounds and N–H stretching frequency shifts upon π-hydrogen bonding.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations